Phase diagram of Ca1−xCexMnO3 thin films studied by X-ray magnetic circular dichroism. (April 2015) - Harano, T.; Shibata, G.; Yoshimatsu, K.; Ishigami, K.; Verma, V.K.; Takahashi, Y.; Kadono, T.; Yoshida, T.; Fujimori, A.; Koide, T.; Chang, F.-H.; Lin, H.-J.; et al.
Abstract: In the perovskite-type Ca1− x Ce x MnO3 (CCMO), one can control the transport and magnetic properties through varying Ce content. In the case of thin films, the properties can also be controlled by epitaxial strain from the substrate through changing it such as YAlO3 (YAO), NdAlO3 (NAO), and LaSrAlO4 (LSAO). However, one cannot measure the magnetization of thin films on NAO substrates by conventional magnetization measurements because of the strong paramagnetic signals from the Nd 3+ ions. In order to eliminate the influence of Nd 3+ and to identify magnetic phases of the CCMO thin films, we have performed element-selective X-ray magnetic circular dichroism (XMCD) measurements of the Mn 2 p core level. By studying the anisotropy of the XMCD intensity, we could unambiguously determine the magnetic phase diagram of the CCMO thin films. Abstract : Highlights: Studies of the magnetic properties of thin films are often prohibited by magnetic substrates. We employed X-ray magnetic circular dichroism to avoid magnetic signals from substrates. The magnetic phase diagram of Ca1− x Ce x MnO3 thin films could be determined.